2019
DOI: 10.3389/fphys.2019.00060
|View full text |Cite
|
Sign up to set email alerts
|

Large Propulsion Demands Increase Locomotor Adaptation at the Expense of Step Length Symmetry

Abstract: There is an interest to identify factors facilitating locomotor adaptation induced by split-belt walking (i.e., legs moving at different speeds) because of its clinical potential. We hypothesized that augmenting braking forces, rather than propulsion forces, experienced at the feet would increase locomotor adaptation during and after split-belt walking. To test this, forces were modulated during split-belt walking with distinct slopes: incline (larger propulsion than braking), decline (larger braking than prop… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
34
2
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
3
1

Relationship

2
7

Authors

Journals

citations
Cited by 32 publications
(42 citation statements)
references
References 82 publications
5
34
2
1
Order By: Relevance
“…altered environment and postadaptation behavior. This finding is consistent with previous work demonstrating that the extent to which subjects adapt their movements during split-belt walking does not predict their aftereffects (Sombric et al, 2019). Partial dissociation between steadystate and postadaptation behavior is further supported by the findings that aftereffects are not sensitive to manipulation of steady-state behavior through visual feedback (Wu et al, 2014;Long et al, 2016).…”
Section: Partial Dissociation Between Recalibration and Execution Of supporting
confidence: 91%
“…altered environment and postadaptation behavior. This finding is consistent with previous work demonstrating that the extent to which subjects adapt their movements during split-belt walking does not predict their aftereffects (Sombric et al, 2019). Partial dissociation between steadystate and postadaptation behavior is further supported by the findings that aftereffects are not sensitive to manipulation of steady-state behavior through visual feedback (Wu et al, 2014;Long et al, 2016).…”
Section: Partial Dissociation Between Recalibration and Execution Of supporting
confidence: 91%
“…We found that stroke survivors exhibited intact recalibration of corrective responses, but impaired muscle patterns at steady state split-belt walking, suggesting partial dissociation between motor performance in the altered environment and post-adaptation behavior. This finding is consistent with previous work demonstrating that the extent to which subjects adapt their movements during split-belt walking does not predict their after-effects (Sombric et al, 2019). Partial dissociation between steady-state and post-adaptation behavior is further supported by the findings that aftereffects are not sensitive to manipulation of steady-state behavior through visual feedback (Wu et al, 2014;Long et al, 2016).…”
Section: Partial Dissociation Between Recalibration and Execution Of supporting
confidence: 91%
“…This does not 480 imply that adaptation cannot occur rapidly with other experimental manipulations. There is evidence that 481 people adopt longer steps with the leg on the fast belt when walking on an inclined split-belt treadmill for 482 10 minutes (Sombric et al, 2019) or when adapting to belt speeds close to running for five minutes 483 (Yokoyama et al, 2018). Given that these studies did not calculate mechanical work, and we do not know 484 what the energetically optimal solution for the above studies would be, we cannot speculate if the rate of 485 adaptation toward the energy optimal behavior occurred more rapidly than in the current study.…”
mentioning
confidence: 99%